Teaching Practise Utilising Embedded Indigenous Cultural Standards - Gilbert, Stephanie; Tillman, Gail (The Australian Journal of Indigenous Education, 2017)
The Wollotuka Institute, University of Newcastle, New South Wales, is the first university or organisation to enter into the accreditation process with the World Indigenous Higher Education Consortium (WINHEC). Part of that process includes identifying the local cultural standards and protocols that drive and shape our work as a cultural entity. As a result of successfully completing these processes, the course ‘Working with Aboriginal Communities’, consciously underwent a process of affirmation recognising and embedding where missing, these cultural protocols within our pedagogy and curriculum. Each intake sees students from all disciplines enrol and all benefit greatly from their cultural learning experiences. In this paper, we discuss how these cultural protocols shaped the course material that both online and face-to-face tertiary students experienced, as well, noting the outcomes of this process. Both authors are long-term educators in higher education and have had our teaching invigorated by this experience of critique and reflection. This paper serves to both be a reflective and documentary process for ourselves as well as an opportunity to share our experiences with our colleagues involved in higher education.